The Parasite: A Story - Doyle, Arthur Conan, 1859-1930 (Salt Lake City, UT : Project Gutenberg, 1995)
"The Parasite: A Story" by Arthur Conan Doyle is a novelette published in 1894. Austin Gilroy, a skeptical young physiologist, encounters Miss Penclosa, a middle-aged woman with psychic powers and a crippled leg. After witnessing her mesmerism abilities, Gilroy allows himself to become the subject of her experiments. But when Miss Penclosa develops feelings for him and he rejects her advances, she begins using her mind control powers for increasingly sinister purposes, leading to a chilling confrontation. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Parasite
Release date is 1995-11-01
Keywords: Horror tales; Mesmerism -- Fiction